Młodzież i jej obecność w przestrzeni cyfrowej w kontekście budowania tożsamości - Pawlaczyk, Jonasz; Dylak, Stanisław (Studia Edukacyjne, 2020)
The text focuses on presenting the issues related to the process of young people’s building and developing identities and on underlining the impact of a broadly understood technology on this process. The very concept of identity, subject to many approaches and theories, is also discussed. The text draws attention to the school and the teacher as elements whose task should be to help students to cope with the challenges that today’s (postmodern) world presents to young people. The goal is to enable the best conditions for self-development and building a stable and mature identity in an ever-changing environment. Technology is not seen only as a threat to man and his identity. However, the lack of a solid theoretical basis, regarding the impact of technology on identity building and preparation of appropriate preventive behavior, increases the risk of a negative impact of technology. The authors of the text strongly believe that changing the paradigm of human behavior can bring about beneficial effects on humanity, on the environment and on the entire planet.